Experimental and Numerical Analysis of Flow Behavior for Reverse Circulation Drill Bit with Inserted Swirl Vanes. (10th January 2022) - Yang, Cheng; Jiang, Jianliang; Qi, Bo; Cui, Guoqing; Zhang, Liyong; Chen, Yunwang; Cao, Pinlu
Abstract : A swirling drill bit designed with an integrated vane swirler was developed to improve reverse circulation in down-the-hole hammer drilling. Its entrainment effect and influential factors were investigated by CFD simulation and experimental tests. The numerical results exhibit reasonable agreement with the experimental data, with a maximum error of 13.68%. In addition, the structural parameters of the swirler were shown to have an important effect on the reverse circulation performance of the drill bit, including the helical angle and number of spiral blades, swirler outlet area, and the flushing nozzles. The optimal parameters for the swirling drill bit without flushing nozzles include a helical angle of 60°, four spiral blades, and the area ratio of 2, while it is about 30°, 3, and 3 for the drill bit with flushing nozzles. Moreover, the entrainment ratio of the drill bit without flushing nozzles can be improved by nearly two times compared with one with flushing nozzles under the same conditions.